2021
DOI: 10.1016/j.clnu.2020.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of folic acid and vitamin-B12 supplementation on fracture risk and cardiovascular disease: Extended follow-up of the B-PROOF trial

Abstract: Background & aims: In the initial B-proof, we found inconsistent results of B vitamin supplementation. However, the debate regarding the effects of B vitamins on age-related diseases continues. Therefore, our aim was to investigate the long-term effects (5e7 years follow-up) of an intervention with folic acid and vitamin-B12 supplementation on fracture and cardiovascular disease risk. Methods: Extended follow-up of the B-PROOF trial, a multi-center, double-blind randomized placebocontrolled trial designed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The most recent Cochrane systematic review and meta-analysis of the effect of t-Hcy lowering by B vitamin supplementation reviewed 15 RCTs of subjects with CHD and stroke as preexisting diseases ( Table 1 ). 64 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 The meta-analysis included RCTs evaluating the occurrence of myocardial infarction and stroke during at least 1 year in patients without end-stage renal disease. 64 This Cochrane meta-analysis observed a small reduction in stroke outcomes with high-quality evidence.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent Cochrane systematic review and meta-analysis of the effect of t-Hcy lowering by B vitamin supplementation reviewed 15 RCTs of subjects with CHD and stroke as preexisting diseases ( Table 1 ). 64 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 The meta-analysis included RCTs evaluating the occurrence of myocardial infarction and stroke during at least 1 year in patients without end-stage renal disease. 64 This Cochrane meta-analysis observed a small reduction in stroke outcomes with high-quality evidence.…”
Section: Introductionmentioning
confidence: 99%
“…S1 [available in the online version]) ( Table 1 ). 64 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 The 5 to 7 year long-term effects of folic acid and vitamin-B12 supplementation had a null effect on CVD risk. 90 In contrast, the percent lowering in t-Hcy was significantly associated with a reduction in the risk of first stroke event in CSPPT Chinese adults with hypertension.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a reciprocal relationship has been shown between vitamin D levels and DNA methylation of genes of the cytochrome P450 family involved in its metabolism [40]. These mechanisms warrant further investigation as interindividual variability could help explain why neither vitamin D nor B12 supplementation have shown to be beneficial for CVD prevention in individuals without deficiencies [41][42][43].…”
Section: Potential and Limitations Of Genotyping For Precision Nutritionmentioning
confidence: 98%
“…The consumption of folic acid and vitamin B-12 is expected to reduce the amount of homocysteine in the blood by a quarter or a third [ 190 ], which would slow down its degradative action on the extracellular matrix and decrease BMD [ 191 ]. However, the results showed that a chronic intake of folic acid and B-12 has no effect on the risk of fracture [ 192 ].…”
Section: Treatment Of Osteoporosis and Novel Approachesmentioning
confidence: 99%